Body Mass Index Trajectories among Middle-Aged and Elderly Canadians and Associated Health Outcomes. (27th January 2016) - Wang, Meng; Yi, Yanqing; Roebothan, Barbara; Colbourne, Jennifer; Maddalena, Victor; Wang, Peizhong Peter; Sun, Guang
Abstract : Background . Whether there is heterogeneity in the development of BMI from middle-age onward is still unknown. The primary aim of this study is to analyze long-term obesity and how BMI trajectories are associated with health outcomes in midlife. Methods . Latent Class Growth Modelling was used to capture the changes in BMI over time. In this study, 3070 individuals from the National Population Health Survey (NPHS), aged 40–55 years at baseline, were included. Results . Four BMI trajectory groups, "Normal-Stable" (N-S), "Overweight-Stable" (OV-S), "Obese I-Stable" (OB I-S), and "Obese II-Stable" (OB II-S), were identified. Men, persons of White ancestry, and individuals who had no postsecondary education had higher odds of being in the latter three groups. Moreover, members of the OV-S, OB I-S, and OB II-S groups experienced more asthma, arthritis, hypertension, diabetes, heart disease, cognitive impairment, and reduced self-rated overall health. Individuals in the OB II-S group were at greater risk for back problems, chronic bronchitis or emphysema, and emotional issues when compared to the N-S group. Conclusion . Understanding different BMI trajectories is important in order to identify people who are at the highest risk of developing comorbidities due to obesity and to establish programs to intervene appropriately.